Avaliação das tensões no estado limite de serviço em seções de concreto protendido - Thiago Pena Bortone (2014)
The worldwide demand for more efficient, durable and esthetically pleasing buildings has increased the use prestressed concrete over the past years. Thus, the behavior of the elements under the effect of prestressing forces must be understood in order to characterize it. In this scenario, the focus of this dissertation is the analysis, under service loads, of post-tensioning concrete beams with bonded strands. A mathematical model based on Brazilian standard NBR 6118 (ABNT, 2007) and in some prescriptions of the Model Code 1978 (CEB-FIP, 1978) is employed to evaluate the stresses in service as well as to classify the prestressing structural degree according to NBR 6118 (ABNT, 2007). This model was developed and implemented using an object-oriented programming language Microsoft Visual Basic. NET. The model was compared to experimental and theoretical results found in the literature. This comparative study was also used as benchmarks to various points of the algorithm. Conclusions are drawn at the end as well as suggestions for future research.